2016
DOI: 10.1063/1.4943353
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll mediated photodynamic inactivation of blue laser on Streptococcus mutans

Abstract: Photodynamic inactivation is an inactivation method in microbial pathogens that utilize light and photosensitizer. This study was conducted to investigate photodynamic inactivation effects of low intensity laser exposure with various dose energy on Streptococcus mutans bacteria. The photodynamic inactivation was achieved with the addition of chlorophyll as photosensitizers. To determine the survival percentage of Streptococcus mutans bacteria after laser exposure, the total plate count method was used. For thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Chlorophyll from the leaf extract can be used as photosensitizer [8]. Astuti et al showed that using chlorophyll and blue diode laser in PDI Streptococcus mutans was able to decrease 78% of colony [9].…”
Section: Introductionmentioning
confidence: 99%
“…Chlorophyll from the leaf extract can be used as photosensitizer [8]. Astuti et al showed that using chlorophyll and blue diode laser in PDI Streptococcus mutans was able to decrease 78% of colony [9].…”
Section: Introductionmentioning
confidence: 99%
“…Destruction of target cells through oxidation mechanisms that cause cell lysis due to inactivation of proteins and membranes [16]. Various studies have shown the success of microbial photoinactivation by photodynamic method [17][18].…”
Section: Introductionmentioning
confidence: 99%
“…12 Another in vitro photodynamic research using 405 nm laser diode by 75 second exposure time (25J.cm -2 energy density) combined with administration of chlorophyll as a photosensitizer with 1,5 cm distance can cause the S. mutant bacteria death, up to 74%. 13 This study was perform to obtain an appropriate energy density of 660nm diode laser in photodynamic inactivation in vitro test with exposure time less than 1 minute using A. actinomycetemcomitans bacteria. This research also aimed to analyze the optimization of bactericide by adding chlorophyll extract derived from Moringa oleifera leaves as an exogenous photosensitizer to increase the ability to absorb light.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain percentage of viability of bacterial colonies, the following formula was used. 13 ∑ colonies of treatment -colonies of control x 100% colonies of control The exposure area characterization was conducted to ensure the exposure area of the diode laser which guided by 8mm multimode optical fiber. The results showed that the exposure area of the 660 nm diode laser was 0.162 ± 0.01 cm 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation